Radiological Imaging of the Kidney - Quaia, Emilio; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
This book, now in its second edition, provides a comprehensive analysis of imaging of the kidneys, upper urinary tract, and ureters, covering the normal anatomy and anatomic variants as well as all renal and urinary system pathologies. The relevant imaging modalities are first discussed, with detailed description of their applications in the kidney and upper urinary tract. The entire spectrum of kidney pathologies is then presented in a series of detailed chapters with up-to-date references, high-quality images, informative schemes, and figures showing macroscopic and microscopic surgical and pathologic specimens. Chapters relating to the latest innovations in tumor ablation, vascular and nonvascular interventional procedures, and parametric and molecular imaging have been fully updated to reflect progress in these rapidly evolving fields. This book will be of great interest to all radiologists, oncologists, nephrologists, and urologists who are involved in the management of kidney pathologies in their daily clinical practice.
Embryology and development of the Kidney -- Normal Radiological Anatomy and Anatomical Variants of the Kidney -- Normal Radiological Anatomy of the Retroperitoneum -- Imaging and Interventional Modalities: Ultrasound of the Kidney -- Computed Tomography -- Magnetic Resonance Imaging -- Nuclear Medicine -- Biopsy -- Vascular Interventional Radiology -- Non-vascular Interventional Radiology -- Non-Tumoral Pathology: Congenital and Development Disorders of the kidney -- Renal Cystic Disease -- Renal Parenchymal Diseases -- Obstructive Uropathy, Pyonephrosis and Reflux Nephropathy in adults -- Nephrolithiasis and Nephrocalcinosis -- Acute Renal Infections -- Chronic renal infections and renal fungal infections -- Renal Vascular Pathologies -- Imaging of Renal Trauma -- Tumoral Pathology: Benign Solid Renal Tumors -- Renal Cell Carcinoma -- Rare and Secondary Tumors of the Kidney and Renal Pseudotumors -- Radiofrequency ablation and cryoablation for renal cell carcinoma -- Urinary tract tumors -- Renal Lymphoma and Renal Sarcomas -- Cystic Renal Masses. Special Topics: The Pediatric Kidney -- The Kidney in the Elderly -- Renal Failure -- Renal Transplant -- Imaging of Dialysis -- Imaging of the Postoperative Kidney -- Contrast Media – Induced Nephropathy and Nephrogenic Systemic Fibrosis -- Functional Imaging of the Kidney -- Molecular Imaging and Tumoral Antigen Targeting -- Research Perspectives and Future Trends in Renal Imaging.
Keywords: Radiology; Nephrology; Urology; Internal medicine; Diagnostic Radiology; Nephrology; Urology; Internal Medicine